Effect of Statin Treatment on Obese Mice Lacking Selenocysteine Lyase. (29th May 2020) - Watanabe, Ligia; Hashimoto, Ann; Torres, Daniel; Berry, Marla; Seale, Lucia
Abstract: Objectives: Americans are a selenium-replete population with high use of statins, a drug commonly prescribed to ameliorate hypercholesterolemia. Statins act by inhibiting the first step of cholesterol biosynthesis in the liver, the mevalonate pathway. This pathway is also important for the maturation of the selenocysteine tRNA, responsible for the expression of selenoproteins. Selenoprotein deficits were suggested as responsible for side effects of statins, such as increased oxidative stress leading to muscle cramps and myopathies. Selenium for selenoprotein synthesis can be provided by diet or by the actions of the selenium recycling enzyme selenocysteine lyase (Scly). Our objective was to investigate the effects of the use of statins in an animal model lacking the enzyme Scly and fed a high-fat, Se-supplemented diet. Methods: Age-matched homozygous littermates wild-type C57BL/6 N (WT) and Scly knockout (Scly KO) mice were fed a high-fat diet containing a 1 ppm blend of selenite plus selenomethionine, and were daily treated with simvastatin (5 mg/kg of body weight) for 21 days. We analyzed serum cholesterol levels, oxidative stress and creatine kinase (CK) activity, and liver and skeletal muscle gene expression of selenoproteins and enzymes involved in creatine metabolism. Results: Obese Scly KO mice had a sex-dependent response statin treatment. While female Scly KO mice improved their body weight after statin treatment, male Scly KO mice further gained weight. Statin treatment improved serum oxidative stress in the Scly KO mice, despite sharp elevation of CK activity. Statin treatment did not affect hepatic selenoprotein gene expression of Scly KO mice, but impaired glutathione peroxidase 1 expression in the muscle of male Scly KO mice, while enhancing it in females. Conclusions: Responses to statin treatment in Scly KO mice fed a high-fat, Se-supplemented diet vary according to sex, benefiting more female than male mice, and are mostly independent of selenoprotein expression. Funding Sources: National Institutes of Health (NIH) grants U54MD007601 Ola Hawaii (subproject 5544) and R01DK47320, and Fundação de Amparo à Pesquisa do Estado de São Paulo fellowship 2018/0, 9478–4. The content is solely the responsibility of the authors and does not necessarily represent the official views of the NIH.